2017
DOI: 10.1016/j.adolescence.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

The differential influence of absent and harsh fathers on juvenile delinquency

Abstract: Researchers have identified father absence as a contributor to juvenile delinquency. Consequently, politicians and community leaders are making efforts to re-engage fathers. However, it is possible that the presence of fathers is not, in itself, a substantial protective factor and, in some cases, can even be more detrimental than father absence. Employing a diverse sample of male juvenile offenders in the U.S. (ages 13-17), the present study examined the differential effects of absent fathers and harsh fathers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 55 publications
0
23
0
5
Order By: Relevance
“…Deviant behavior in schools with less formation ability of self-discipline, controlling behavior and requires the guidance of teachers are, among others, delays, ditching, against teachers, fights, cheating and so on (Bishop et al, 2018;Conrad, 2017;Moffitt, 2017). Deviant behavior that commonly occurs in adolescents is also often said to be juvenile delinquency (Hawkins & Weis, 2017;Hoffmann & Dufur, 2018;Plantz & Garbarino, 2017;Simmons, Steinberg, Frick, & Cauffman, 2018;Sykes & Matza, 2017). Students who violate the discipline cannot be responsible for the study, this will damage potential, talents, abilities, ideals, and their future.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deviant behavior in schools with less formation ability of self-discipline, controlling behavior and requires the guidance of teachers are, among others, delays, ditching, against teachers, fights, cheating and so on (Bishop et al, 2018;Conrad, 2017;Moffitt, 2017). Deviant behavior that commonly occurs in adolescents is also often said to be juvenile delinquency (Hawkins & Weis, 2017;Hoffmann & Dufur, 2018;Plantz & Garbarino, 2017;Simmons, Steinberg, Frick, & Cauffman, 2018;Sykes & Matza, 2017). Students who violate the discipline cannot be responsible for the study, this will damage potential, talents, abilities, ideals, and their future.…”
Section: Introductionmentioning
confidence: 99%
“…Students who violate the discipline cannot be responsible for the study, this will damage potential, talents, abilities, ideals, and their future. So that the behavior of students who violate disciplines will hinder the achievement of national education goals, which is to the intellectual life of the nation and developing the whole person, the man whose faith and fear of God Almighty and noble character, has the knowledge and skill, physical and spiritual health, personality stable and independent, as well as a sense of responsibility and national community (Plantz & Garbarino, 2017;Simmons et al, 2018;Sykes & Matza, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Komunikasi yang terjalin antara orangtua-remaja menjadi hal yang penting terutama berperan dalam pembentukan pribadi remaja. Seperti dalam suatu hasil penelitian yang mengidentifikasi bahwa ketidakhadiran ayah bisa menjadi kontributor maraknya kenakalan remaja, artinya peran ayah dan ibu tetap dibutuhkan untuk tumbuh-kembang anak remajanya (Simmons, Steinberg, Frick, & Cauffman, 2018).…”
unclassified
“…It has been reported that childhood and adolescent development is positively enhanced by both parents participating in the upbringing of their children. In the absence of a father the differences can be seen in development where girls exhibit an earlier onset of menarche (Guardia, Nelson, & Lertora, 2014) and in boys there can be behavioural problems such a delinquency (Simmons, Steinberg, Frick, & Cauffman, 2018) or other risky behaviours such a substance use and multiple sexual partnerships (Alleyne-Green, Grinnell- Davis, Clark, Quinn, & Cryer-Coupet, 2016). The perceptions of love and sexual relationships as expressed by the participants of this study may be strongly influenced by parents being absent.…”
Section: Discussionmentioning
confidence: 77%